Extraction and characterization of soluble non-digestible polysaccharides from coconut kernel cake and palm kernel cake as potential source of prebiotics - Bello, Bashirat (2017)
The health benefits associated with consumption of prebiotic and probiotics have made it more preferable than conventional food products. Extraction of prebiotics from local plant materials are associated with low yield; therefore, the aim of this research is to study the effects of solvents on extraction yield and biochemical composition of soluble polysaccharides from palm kernel cake (PKC) and coconut kernel cake (CKC) that could have prebiotics potential. The specific objectives are, (i) To extract and characterized soluble polysaccharides from palm kernel cake and coconut kernel cake (ii) To determined the non-digestibility of the extracted soluble polysaccharides on artificial human gastric juice and alpha amylase and, (iii) To evaluate the prebiotics potential on Lactobacillus plantarum ATCC 8014 and Lactobacillus rhamnosus ATCC 53103 in-vitro. Towards achieving these objectives, three different solvents namely water, citric acid and NaOH were employed to extract soluble polysaccharide from PKC and CKC. The chemical properties of the extracted soluble polysaccharides which include total carbohydrates, protein content, solubility rate, monosaccharides composition, structural information and thermal properties were determined. The extracted soluble polysaccharides were further subjected to digestibility test using artificial human gastric juice and alpha amylase. Their prebiotic potential was determined on Lactobacillus plantarum ATCC 8014 and Lactobacillus rhamnosus ATCC 53103 as probiotics strains in-vitro. It was observed that, there were significant differences (P<0.05) among the crude polysaccharides extracted with the three different solvents. In both PKC and CKC, NaOH had the highest percentage polysaccharides yield (8.73 and 2.90%), whereas the lowest percentage yield of soluble polysaccharide obtained was recorded using hot water in both PKC and CKC. The soluble polysaccharides obtained from PKC and CKC, (PKCSP) and (CKCSP) respectively, were found to contain a considerable percentage composition of total carbohydrates 57.11%, 56.94% and 50.95% for water, citric acid and NaOH in PKC samples. In CKC, the total percentage carbohydrate composition for water, citric acid and NaOH were 55.26%, 42.56% and 43.46% respectively, with traces of proteins ranging from 0.39 to 0.72% in all the soluble polysaccharides. The extracted crude polysaccharides from both PKC and CKC were found to be highly soluble with an average solubility rate of 98%. There was no significant difference (P>0.05) between the solubility rate of PKCSP and CKCSP in all solvents extracts.The polysaccharides of both PKCSP and CKCSP composed of mannose, glucose, galactose, arabinose with traces of rhamnose and xylose as revealed by GC-FID. The highest monosaccharaides contents were glucose in CKCSP (78%) and mannose in PKCSP (64%) in water and citric acid as extracts respectively. FTIR spectroscopy revealed that the polysaccharides extracts were linked together by β and α-glycosidic bonds with absorption bands at around 1072 cm-1 and 888 cm-1, with traces of protein in water extracts at around 1534 cm- 1.Thermal analysis revealed by differential scanning calorimeter (DSC) showed the main degradation temperature of both polysaccharides at around 120 °C to 130 °C. PKCSP and CKCSP were found to be highly resistance (>96%) when subjected to artificial human gastric juice. There was no significant differences (P>0.05) of the percentage hydrolysis observed from non-digestibility tests on artificial human gastric juice among the tested polysaccharides extracts. The prebiotics potentials of the polysaccharides on probiotics in-vitro revealed an increase in growth of Lactobacillus plantarum ATCC 8014 and Lactobacillus rhamnosus ATCC 53103 with decrease in the pH of the medium, indicating that short chain fatty acid (SCFA) were produced at the end of the incubation period when compared with the fructooligosaccharides (FOS) control. It can be concluded that soluble polysaccharides from PKC and CKC were highly resistance to artificial human gastric juice and were able to increase the growth of the tested probiotics in-vitro. It can be concluded that, the highest yield of soluble polysaccharides was obtained when NaOH was used as an extracting solvent. But this extract exhibited lower percentage of monosaccharides composition as compared to water and citric acid extracts in both PKC and CKC samples. In general, results from this study demonstrated that soluble polysaccharides obtained from PKC and CKC could be used as potential prebiotics.